2000
DOI: 10.1002/(sici)1097-4628(20000222)75:8<1026::aid-app7>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Formation and analysis of a polyimide layer in composite membranes

Abstract: ABSTRACT:Composite membranes containing a thin-film layer of aromatic polyimides (PI) ensure an advantageous combination of selectivity and permeability in gas separation. A series of rigid-chain PI with different chemical structures were studied as a thin active layer. Composite membranes were prepared by coating a solution of poly-(amic acid) (PAA) and an imidization catalyst on a poly(phenylene oxide) (PPO) support with pores filled by decane. The subsequent stage of solid-state catalytic transformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Several polymer-C 60 composites, namely C 60 plus polyethylene [12], polystyrene [13], acrylic [14][15][16][17] or vinyl polymers [18], etc., have been studied. Polyimides (PIs) are high-temperature polymers, exhibiting a wide range of applications, as for example, in the preparation of films [19], fibers [20], foams [21] and membranes [22]. Recently, combinations of polyimides (PIs) with fullerene C 60 have received some attention [23,24] due to their interesting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several polymer-C 60 composites, namely C 60 plus polyethylene [12], polystyrene [13], acrylic [14][15][16][17] or vinyl polymers [18], etc., have been studied. Polyimides (PIs) are high-temperature polymers, exhibiting a wide range of applications, as for example, in the preparation of films [19], fibers [20], foams [21] and membranes [22]. Recently, combinations of polyimides (PIs) with fullerene C 60 have received some attention [23,24] due to their interesting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of new polymers for membranes with high performance and selectivity is of scientific and practical significance. Aromatic polyimides have many valuable physicomechanical properties and improved chemical and thermal stability, which are important for their use in gas separation and ultrafiltration and microfiltration 1–3. The specific chemical structure of polyimides profoundly affects liquid mixture separation by pervaporation (PV).…”
Section: Introductionmentioning
confidence: 99%
“…A number of attempts have been made to fabricate composite polyimide membranes from poly(amic acid), PAA, precursors. Poly(amic acid) polymers are frequently processed into the target article utilizing aggressive aprotic solvents, such as DMF. This makes it difficult to form composite membranes from PAA precursors.…”
Section: Introductionmentioning
confidence: 99%
“…For this and other reasons, fabrication of composite polyimide membranes from the poly(amic acid) precursors has achieved limited success. Most recently, Polotskaya et al reported fabrication of composite polyimide membranes from poly(amic acid) solutions containing large amounts of imidazole or benzimidazole. , They found that the use of these specific membrane casting compositions significantly lowered the imidization temperature. However, the authors used a high-temperature boiling solvent, DMF, and a nonvolatile catalyst in composite membrane preparation that presented severe drawbacks.…”
Section: Introductionmentioning
confidence: 99%